Application of MCKD-cyclic Domain Demodulation Method in Gearbox Fault Diagnosis - Wang Zhijian; Wang Junyuan; Zeng Zhiqiang; Zhang Jiping (Jixie chuandong)
The cross- term interference caused by multi- modulator and multi- carrier makes it limited the use of the cyclic autocorrelation demodulation. A new method called the MCKD（ Maximum correlated Kurtosis Deconvolution）- cyclic domain demodulation is proposed. Firstly,the strong background noise of the original signal is decreased by the MCKD method in order to extract the interest period component,the above given signal is processed by the cyclic autocorrelation function demodulation. The new method can decrease the cross- term interference caused by multi- modulator and multi- carrier and improve the reliability of the analysis. As the application of the MCKD- cyclic domain demodulation theory in fault diagnosis,the method is used to extract fault feature from vibration signals successfully.